Partnership as a legal form of exercising the profession of midwife - Sadowska Monika (Pielęgniarstwo XXI Wieku, 2017)
Introduction. The profession of midwife belongs to the medical ones. In the Polish legal system, the definition it is not of a legislative nature. It refers to liberal professions associated with practical medical knowledge. However, the profession of midwife has also been included in the catalog of liberal professions under the commercial law, and the legislature allows the practice of midwife in the form of a partnership.